Self-repairing solid electrolyte membrane, preparation method thereof, solid-state battery and mechanical device

By introducing organic frameworks and polymeric monomers into the solid electrolyte membrane, a self-healing solid electrolyte membrane is solved, and the existing membranes have shortcomings in mechanical properties and ionic conductivity are achieved, higher mechanical strength and ionic conductivity are achieved, and the membrane is self-healing ability is imparted.

CN119674213AActive Publication Date: 2025-03-21CHONGQING TALENT NEW ENERGY CO LTD

Patent Information

Application Number
CN202411940033.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing solid polymer electrolyte membranes have shortcomings in mechanical properties and ionic conductivity, and are easily penetrated by dendrites, resulting in a decrease in electrochemical properties.

Method used

A self-healing solid electrolyte membrane is adopted, which consists of an organic framework and a polymer electrolyte. The polymer electrolyte is formed by polymerizing monomers and lithium salts in the pores of the organic framework. The polymeric monomers contain S-S bonds, C-O bonds and C=C bonds, which improves the mechanical properties and ionic conductivity of the membrane.

Benefits of technology

The mechanical properties and ionic conductivity of the solid electrolyte membrane are improved, the mechanical strength of the membrane and the conduction ability of lithium ions are enhanced, the risk of penetration by dendrites is reduced, and the membrane is given self-healing ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_39
    Figure SMS_39
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The invention provides a self-repairing solid electrolyte membrane, a preparation method thereof, a solid-state battery and a mechanical device. The self-repairing solid electrolyte membrane comprises an organic framework and a polymer electrolyte, pores of the organic framework are filled with the polymer electrolyte, the polymer electrolyte is formed by polymerizing a polymeric monomer and a first lithium salt in the pores of the organic framework, the polymeric monomer contains a self-repairing S-S bond, and the first lithium salt contains a second lithium salt. The polymeric monomer also contains a C-O bond and a C = C bond. Therefore, the self-repairing solid-state electrolyte membrane has excellent mechanical properties and high ionic conductivity, and the solid-state battery prepared by adopting the self-repairing solid-state electrolyte membrane has high energy density, long cycle life and reliable safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a self-repairing solid-state electrolyte membrane and a preparation method thereof, a solid-state battery and a mechanical device. Background Art

[0002] The flammability and leakage of liquid electrolytes commonly used in lithium-ion batteries pose serious safety risks to batteries. The emergence of solid electrolytes can better solve the safety issues of the above liquid electrolytes. Solid electrolytes have flame retardant properties and can greatly improve battery safety.

[0003] Solid polymer electrolyte is a type of solid electrolyte, which is widely used in solid-state batteries due to its good flexibility and good contact with electrodes. However, the low ionic conductivity and poor mechanical properties of solid polymer electrolytes make them easily penetrated by dendrites, thus greatly reducing the electrochemical performance of the battery. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the prior art at least to some extent. To this end, one object of the present invention is to provide a self-repairing solid electrolyte membrane and a preparation method thereof, a solid-state battery and a mechanical device.

[0005] In a first aspect of the present invention, the present invention provides a self-repairing solid electrolyte membrane. According to an embodiment of the present invention, the self-repairing solid electrolyte membrane comprises: Organic framework; A polymer electrolyte is filled in the pores of the organic skeleton. The polymer electrolyte is formed by polymerizing a polymer monomer and a first lithium salt in the pores of the organic skeleton. The polymer monomer contains a self-repairing SS bond, and the polymer monomer also contains a CO bond and a C=C bond.

[0006] According to the present invention, the self-repairing solid electrolyte membrane includes an organic skeleton and a polymer electrolyte, the polymer electrolyte is filled in the pores of the organic skeleton, the organic skeleton provides mechanical support, and enhances the mechanical properties of the solid polymer electrolyte membrane. The polymer electrolyte is formed by polymerization of a polymer monomer and a first lithium salt in the pores of the organic skeleton, and the polymer monomer contains SS bonds, CO bonds, and C=C bonds. The double bond (C=C) in the polymer monomer enables the above self-polymerization to be realized, and the polymerization reaction is carried out in the pores of the organic skeleton. The polymer monomer can be tightly connected and fully fill the pores of the organic skeleton to form a dense and continuous integrated polymer electrolyte structure. The self-polymerization in the pores of the organic skeleton not only improves the interfacial compatibility between the polymer electrolyte and the organic skeleton, and improves the rapid conduction ability of lithium ions, but also the integrated polymer electrolyte structure can improve the mechanical strength of the solid polymer electrolyte membrane, effectively reducing the risk of being penetrated by lithium dendrites. The polymer monomer contains disulfide bonds (SS), which have the ability to break and reorganize, thus giving the solid polymer electrolyte membrane the ability to self-repair and improving the mechanical stability of the solid polymer electrolyte membrane. In addition, the introduction of sulfur-containing (-S) groups can derive a solid electrolyte interface phase (SEI film formation) that is stable to lithium, thereby better inhibiting lithium dendrites. At the same time, the polymer monomer also contains ether bonds (CO), which increase the Li + The action site increases the Li + The transmission capacity of the solid polymer electrolyte membrane is improved, thereby improving the ionic conductivity of the solid polymer electrolyte membrane. As a result, the self-healing solid electrolyte membrane has excellent mechanical properties and high ionic conductivity.

[0007] In addition, the self-repairing solid electrolyte membrane according to the above embodiment of the present invention also has the following technical features: In some embodiments of the present invention, the polymerizable monomer is selected from at least one of the compounds represented by Formula 1 and the compounds represented by Formula 2; , where -R 1 、-CH 3 、-SSR 2 Group in Replace any position on R 1 is selected from hydrogen or methyl, R 2 An alkyl group or an epoxy group selected from C1-C5; , where -R 3 、-CH 3 -SSR 4 Group in Replace any position on R 3 is selected from hydrogen or methyl, R 4 Selected from C1-C5 alkyl or epoxy.

[0008] In some embodiments of the present invention, R 2 Selected from methyl, ethyl, propyl, butyl, , or .

[0009] In some embodiments of the present invention, R 4 Selected from methyl, ethyl, propyl, butyl, or .

[0010] In some embodiments of the present invention, the compound represented by Formula 1 comprises at least one of the following structures: , , , , , .

[0011] In some embodiments of the present invention, the compound represented by Formula 2 comprises at least one of the following structures: , , , .

[0012] In some embodiments of the present invention, the organic framework includes a polymer and a second lithium salt.

[0013] In some embodiments of the present invention, the organic framework is a fibrous structure.

[0014] In some embodiments of the present invention, the porosity of the organic framework is 60% to 80%.

[0015] In some embodiments of the present invention, the polymer includes at least one of polystyrene, poly-2,6-dimethyl-1,4-phenylene oxide, polyimide, poly-1,4-phenylene sulfide, polyphthalaldehyde, polystyrene-acrylonitrile, polystyrene-butadiene, polyphenylmethylsiloxane, polystyrene-allyl alcohol, polyvinyl benzene sulfide, poly-4-butyltriphenylamine, polystyrene-divinylbenzene, poly-4-vinylpyridine-styrene, polybis(4-phenyl)(4-butylphenyl)amine and polysulfone, preferably poly-1,4-phenylene sulfide and polyvinyl benzene sulfide.

[0016] In some embodiments of the present invention, based on the total mass of the organic skeleton, the mass proportion of the second lithium salt is 5-50%, preferably 20-50%.

[0017] In some embodiments of the present invention, based on the total mass of the polymer electrolyte, the mass proportion of the first lithium salt is 5-50%, preferably 20-50%.

[0018] In some embodiments of the present invention, the polymer electrolyte further comprises an inorganic filler. Based on the total mass of the polymer electrolyte, the mass proportion of the inorganic filler is 5-30%, preferably 20-30%.

[0019] In some embodiments of the present invention, the thickness of the self-healing solid electrolyte membrane is 50 μm-80 μm.

[0020] In a second aspect of the present invention, the present invention provides a method for preparing the self-healing solid electrolyte membrane. According to an embodiment of the present invention, the method comprises: The organic skeleton is immersed in a mixed solution containing a polymerized monomer, a first lithium salt, an initiator and a first solvent, and then dried to obtain a self-repairing solid electrolyte membrane.

[0021] According to the preparation method of the above embodiment of the present invention, the organic skeleton is immersed in a mixed solution containing a polymerized monomer, a first lithium salt, an initiator and a first solvent, and then dried. The organic skeleton provides mechanical support and enhances the mechanical properties of the solid polymer electrolyte membrane. Through drying, under the action of the initiator, the polymerized monomer undergoes a polymerization reaction, and the polymerization reaction is carried out in the pores of the organic skeleton. The polymerized monomer can be tightly connected and fully fill the pores of the organic skeleton to form a dense and continuous integrated polymer electrolyte structure. The self-polymerization in the pores of the organic skeleton not only improves the interfacial compatibility between the polymer electrolyte and the organic skeleton, and improves the rapid conduction ability of lithium ions, but also the integrated polymer electrolyte structure can also improve the mechanical strength of the solid polymer electrolyte membrane, effectively reducing the risk of being penetrated by lithium dendrites. Therefore, the method can be used to prepare a self-healing solid electrolyte membrane with high ion conductivity and excellent mechanical properties.

[0022] In addition, the method for preparing a self-repairing solid electrolyte membrane according to the above embodiment of the present invention also has the following technical features: In some embodiments of the present invention, the mass proportion of the first solvent in the mixed solution is 70% to 90%, preferably 70% to 80%.

[0023] In some embodiments of the present invention, the drying temperature is 60°C to 100°C, preferably 60°C to 80°C.

[0024] In some embodiments of the present invention, the soaking time is 5 min to 10 min, and the temperature is 25° C. to 30° C.

[0025] In some embodiments of the present invention, the method for preparing the organic skeleton comprises: dissolving a polymer and a second lithium salt in a second solvent and then performing melt-blowing to obtain the organic skeleton.

[0026] In a third aspect of the present invention, the present invention provides a solid-state battery. According to an embodiment of the present invention, the solid-state battery comprises the self-repairing solid-state electrolyte membrane or the self-repairing solid-state electrolyte membrane prepared by the above method. Thus, the solid-state battery has high energy density, long cycle life and reliable safety.

[0027] In a fourth aspect of the present invention, the present invention provides a mechanical device. According to an embodiment of the present invention, the mechanical device includes the above-mentioned solid-state battery. As a result, the mechanical device has a long driving range and service life. DETAILED DESCRIPTION

[0028] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0029] In a first aspect of the present invention, the present invention provides a self-repairing solid electrolyte membrane. According to an embodiment of the present invention, the self-repairing solid electrolyte membrane comprises: Organic framework; A polymer electrolyte is filled in the pores of the organic skeleton. The polymer electrolyte is formed by polymerizing a polymer monomer and a first lithium salt in the pores of the organic skeleton. The polymer monomer contains a self-repairing SS bond, and the polymer monomer also contains a CO bond and a C=C bond.

[0030] According to the present invention, the self-healing solid electrolyte membrane includes an organic skeleton and a polymer electrolyte, the polymer electrolyte is filled in the pores of the organic skeleton, the organic skeleton provides mechanical support, and enhances the mechanical properties of the solid polymer electrolyte membrane. The polymer electrolyte is formed by polymerization of a polymer monomer and a first lithium salt in the pores of the organic skeleton, the polymer monomer contains a self-healing SS bond, and the polymer monomer also contains a CO bond and a C=C bond. The double bond (C=C) in the polymer monomer enables the above self-polymerization to be realized, the polymerization reaction is carried out in the pores of the organic skeleton, the polymer monomer can be closely connected, fully fill the pores of the organic skeleton, and form a dense and continuous integrated polymer electrolyte structure. The self-polymerization in the pores of the organic skeleton not only improves the interfacial compatibility between the polymer electrolyte and the organic skeleton, and improves the rapid conduction ability of lithium ions, but also the integrated polymer electrolyte structure can improve the mechanical strength of the solid polymer electrolyte membrane, effectively reducing the risk of being penetrated by lithium dendrites. The polymer monomer contains disulfide bonds (SS), which have the ability to break and reorganize, thus giving the solid polymer electrolyte membrane the ability to self-repair and improving the mechanical stability of the solid polymer electrolyte membrane. In addition, the introduction of sulfur-containing (-S) groups can derive a solid electrolyte interface phase (SEI film formation) that is stable to lithium, thereby better inhibiting lithium dendrites. At the same time, the polymer monomer also contains ether bonds (CO), which increase the Li+ The action site increases the Li + The transmission capacity of the self-repairing solid electrolyte membrane is improved, thereby improving the ionic conductivity of the self-repairing solid electrolyte membrane. As a result, the self-repairing solid electrolyte membrane has excellent mechanical properties and high ionic conductivity.

[0031] It should be noted that the first lithium salt is a conventional material in the art, and those skilled in the art can select it according to actual conditions. For example, the first lithium salt includes but is not limited to LiTFSI, LiFSI, LiClO 4 、LiPF 6 、LiAsF 6 , LiBF 4 、LiPF 4 , LiBOB, LiFAB, LiODFB, LiDODFP, LiOTFP and LiTf.

[0032] According to an embodiment of the present invention, the polymerizable monomer is selected from the compound represented by Formula 1, , where -R 1 、-CH 3 、-SSR 2 Group in Replace any position on R 1 is selected from hydrogen or methyl, R 2 Selected from C1-C5 alkyl or epoxy.

[0033] Furthermore, R 2 Selected from methyl, ethyl, propyl, butyl, , or .

[0034] As an example, the compound represented by the general formula 1 includes but is not limited to at least one of the following structures: , , , , , .

[0035] According to an embodiment of the present invention, the polymerizable monomer is selected from the compound represented by Formula 2, , where -R 3 、-CH 3 -SSR 4 Group in Replace any position on R 3 is selected from hydrogen or methyl, R 4 Selected from C1-C5 alkyl or epoxy.

[0036] Furthermore, R4 Selected from methyl, ethyl, propyl, butyl, or .

[0037] As an example, the compound represented by the general formula 2 includes but is not limited to at least one of the following structures: , , , .

[0038] According to an embodiment of the present invention, the porosity of the organic skeleton is 60% to 80%. The porosity of the organic skeleton is within the above range, which can ensure that the self-repairing solid electrolyte membrane has an appropriate amount of polymer electrolyte, thereby ensuring the high ionic conductivity of the self-repairing solid electrolyte membrane. At the same time, the porosity within the above range ensures the support strength of the organic skeleton, thereby improving the overall mechanical properties of the self-repairing solid electrolyte membrane.

[0039] Furthermore, the organic skeleton is a fibrous structure. The fibrous structure of the organic skeleton has high porosity and specific surface area, thereby promoting a better penetration effect of the polymer electrolyte and improving the filling efficiency. The dense and uniform pores further promote the uniform distribution of the polymer electrolyte in the organic skeleton. At the same time, the organic skeleton also has high mechanical strength and toughness, which significantly enhances the mechanical stability of the solid polymer electrolyte membrane.

[0040] According to an embodiment of the present invention, the organic skeleton includes a polymer and a second lithium salt. By adding the second lithium salt to the organic skeleton, the ionic conductivity of the organic skeleton can be improved, thereby improving the ionic conductivity of the entire self-healing solid electrolyte membrane.

[0041] It should be noted that the second lithium salt is a conventional material in the art, and those skilled in the art can select it according to actual conditions. For example, the second lithium salt includes but is not limited to LiTFSI, LiFSI, LiClO 4 、LiPF 6 、LiAsF 6 , LiBF 4 、LiPF 4 , LiBOB, LiFAB, LiODFB, LiDODFP, LiOTFP and LiTf.

[0042] According to an embodiment of the present invention, the polymer includes at least one of polystyrene, poly-2,6-dimethyl-1,4-phenylene oxide, polyimide, poly-1,4-phenylene sulfide, polyphthalaldehyde, polystyrene-acrylonitrile, polystyrene-butadiene, polyphenylmethylsiloxane, polystyrene-allyl alcohol, polyvinyl benzene sulfide, poly-4-butyltriphenylamine, polystyrene-divinylbenzene, poly-4-vinylpyridine-styrene, poly-bis(4-phenyl)(4-butylphenyl)amine and polysulfone, preferably poly-1,4-phenylene sulfide and polyvinyl benzene sulfide. By using the above-mentioned hard organic matter containing benzene as an organic skeleton, the mechanical properties of the electrolyte membrane can be improved, and the above-mentioned organic skeleton can better inhibit dendrite penetration. The polymer electrolyte formed by self-polymerization of the polymer monomers in the above-mentioned organic skeleton not only has a self-repairing function, but the polymer monomers and the organic skeleton can better synergistically improve the mechanical stability of the entire electrolyte membrane. In particular, organic skeletons such as poly 1,4-phenylene sulfide and polyvinyl phenylene sulfide can chemically interact with the polymer monomers, significantly improving the interfacial compatibility between the organic skeleton and the polymer electrolyte, and further improving the lithium ion transmission capacity, thereby improving the ionic conductivity and mechanical stability of the entire electrolyte membrane.

[0043] According to an embodiment of the present invention, based on the total mass of the organic skeleton, the mass proportion of the second lithium salt is 5-50%, preferably 20-50%. Controlling the mass proportion of the second lithium salt within the above range not only ensures the support strength of the organic skeleton, but also improves the ionic conductivity of the organic skeleton, and better cooperates with the first lithium salt in the polymer electrolyte to play a role, thereby improving the ionic conductivity of the self-healing solid electrolyte membrane.

[0044] According to an embodiment of the present invention, based on the total mass of the polymer electrolyte, the mass proportion of the first lithium salt is 5-50%, preferably 20-50%. Controlling the mass proportion of the first lithium salt within the above range can improve the ionic conductivity of the polymer electrolyte and better cooperate with the first lithium salt in the organic framework, thereby improving the ionic conductivity of the self-healing solid electrolyte membrane.

[0045] According to an embodiment of the present invention, the polymer electrolyte further comprises an inorganic filler. Based on the total mass of the polymer electrolyte, the mass proportion of the inorganic filler is 5-30%, preferably 20-30%.

[0046] As an example, the inorganic filler includes at least one of the following compounds: (I) P p O q , 1≤p≤2, 1≤q≤3, P is at least one of Si, Al, Ni, Ca, Mg, Ti, La or Zr; (II) (X) x O.Al 2 O 3 ySiO2 ·zH 2 O, x = 1 or 2, y ≥ 2, X is at least one of Na, K, Ca or Ba; (III) Li 7-a La 3 Zr 2-a A a O 12 , 0≤a≤2, A is at least one of Ta, Nb, Sn, B, Ba, Zr, Cr, Si, Gd, In, Cu, Mo, Ge, Co, Mn, Sr, Ca, Mg, Sc, Zn, Bi, Sb, Ni, Te, Se, Ti, V, W, Hf or Y; (IV) Li 7-3b B b La 3 Zr 2 O 12 , 0≤b≤0.4, B is at least one of Al, Ga or Fe; (V) Li 7-c La 3- c C c Zr 2 O 12 , 0≤c≤0.8, C is at least one of Ce or Y; (VI) Li 1+m M m Ti 2-m (PO 4 ) 3 , 0≤m<2, M is at least one of Al, Ge, In, La, Y, Ga or Lu; (VII) Li 0.5-3n La 0.5+n TiO 3 , 0 <n<0.15;(Ⅷ)Li 6.6 La 2.75 Y 0.25 Zr 1.6 Ta 0.4 O 12 , Li 6.29 Al 0.07 La 3 Zr 1.75 Te 0.25 O 12 , Li 6.65 Ga 0.15 La 3 Zr 1.9 Sc 0.1 O 12 , Li 5.9 Al 0.2 La 3 Zr 1.75 W 0.25 O 12 、LiZr2 (PO 4 ) 3 , Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 , Li 1.4 Al 0.4 Ti 1.4 Ge 0.2 (PO 4 ) 3 , Li 3 Ln 3 Ta 2 O 12 or (Li 0.33 La 0.56 ) 1.005 Ti 0.99 Al 0.01 O 3 At least one of .

[0047] According to an embodiment of the present invention, the thickness of the self-repairing solid electrolyte membrane is 50 μm to 80 μm. Controlling the thickness of the self-repairing solid electrolyte membrane within the above range can not only ensure the mechanical strength of the self-repairing solid electrolyte membrane, but also give full play to the ion transport performance of the electrolyte, thereby improving the lithium ion conduction capacity of the self-repairing solid electrolyte membrane.

[0048] In a second aspect of the present invention, the present invention provides a method for preparing the self-healing solid electrolyte membrane. According to an embodiment of the present invention, the method comprises: The organic skeleton is immersed in a mixed solution containing a polymerized monomer, a first lithium salt, an initiator and a first solvent, and then dried to obtain a self-repairing solid electrolyte membrane.

[0049] According to the preparation method of the above embodiment of the present invention, the organic skeleton is immersed in a mixed solution containing a polymerized monomer, a first lithium salt, an initiator and a first solvent, and then dried. The organic skeleton provides mechanical support and enhances the mechanical properties of the self-healing solid electrolyte membrane. Through drying, under the action of the initiator, the polymerized monomer undergoes a polymerization reaction, and the polymerization reaction is carried out in the pores of the organic skeleton. The polymerized monomer can be tightly connected and fully fill the pores of the organic skeleton to form a dense and continuous integrated polymer electrolyte structure. The self-polymerization in the pores of the organic skeleton not only improves the interfacial compatibility between the polymer electrolyte and the organic skeleton, and improves the rapid conduction ability of lithium ions, but also the integrated polymer electrolyte structure can also improve the mechanical strength of the self-healing solid electrolyte membrane, effectively reducing the risk of being penetrated by lithium dendrites. Thus, the method can be used to prepare a self-healing solid electrolyte membrane with high ion conductivity and excellent mechanical properties.

[0050] It should be noted that the initiator and the first solvent are conventional materials in the art, and those skilled in the art can select them according to actual conditions. For example, the initiator includes but is not limited to azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovaleronitrile, dimethyl azobisisobutyrate, di-tert-butyl azodicarboxylate, and diisopropyl azodicarboxylate. The first solvent includes but is not limited to at least one of dimethylformamide, N,N-dimethylpyrrolidone, dimethyl sulfoxide, dimethylacetamide, diethyl carbonate, dimethyl carbonate, and ethylene carbonate.

[0051] According to an embodiment of the present invention, the mass proportion of the first solvent of the mixed solution is 70% to 90%, preferably 70% to 80%. By controlling the addition amount of the first solvent of the mixed solution within the above range, the polymer precursor mixed solution can quickly infiltrate the organic skeleton and evenly and fully fill the pores of the organic skeleton.

[0052] According to an embodiment of the present invention, the drying temperature is 60°C to 100°C, preferably 60°C to 80°C. For example, the drying temperature is 60°C, 70°C, 80°C, 90°C, 100°C, etc., or a range between any two of the above values. By controlling the drying temperature within the above range, it can be ensured that the polymerization monomers fully undergo self-polymerization reaction to form a continuous and dense electrolyte, and it can also ensure that the first solvent is fully volatilized.

[0053] According to an embodiment of the present invention, the soaking time is 5 min to 10 min, and the temperature is 25° C. to 30° C. By controlling the soaking time and temperature within the above range, the polymer precursor mixture can evenly and fully fill the pores of the organic skeleton to form a composite structure supported by the organic skeleton and filled with a self-healing electrolyte.

[0054] According to an embodiment of the present invention, the method for preparing the organic skeleton comprises: dissolving a polymer and a second lithium salt in a second solvent and then performing melt-blowing to obtain the organic skeleton.

[0055] As an example, the screw temperature of meltblowing is 180°C and the pulling speed is 50 min -1 .

[0056] Therefore, the method can be used to prepare a self-healing solid electrolyte membrane with excellent mechanical properties and high ionic conductivity, and the method is simple in process, low in cost, and suitable for popularization and application. It should be noted that the characteristics and advantages described above for the self-healing solid electrolyte membrane are also applicable to this method, and will not be repeated here.

[0057] In the third aspect of the present invention, the present invention proposes a solid-state battery. According to an embodiment of the present invention, the solid-state battery comprises the self-repairing solid-state electrolyte membrane or the self-repairing solid-state electrolyte membrane prepared by the above method. As a result, the solid-state battery has high energy density, long cycle life and reliable safety. It should be noted that the features and advantages described above for the self-repairing solid-state electrolyte membrane and its preparation method are also applicable to the solid-state battery, and will not be repeated here.

[0058] According to an embodiment of the present invention, a solid-state battery includes a positive electrode sheet, a self-repairing solid electrolyte membrane and a negative electrode sheet.

[0059] As an example, the main material of the positive electrode plate includes but is not limited to one or more combinations of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and lithium vanadium phosphate; the main material of the negative electrode plate includes but is not limited to one or more combinations of graphite, graphene, carbon nanotubes, silicon-based alloys, silicon-oxygen negative electrodes, silicon-carbon negative electrodes, lithium metal, lithium alloy negative electrodes, lithium titanium oxides, transition metal oxides, and transition metal sulfides.

[0060] In a fourth aspect of the present invention, the present invention proposes a mechanical device. According to an embodiment of the present invention, the mechanical device includes the above-mentioned solid-state battery. As a result, the mechanical device has a long driving range and service life. It should be noted that the features and advantages described above for the solid-state battery are also applicable to the mechanical device and will not be repeated here.

[0061] According to an embodiment of the present invention, the mechanical device includes but is not limited to a motorcycle, a car, a truck, a ship, etc.

[0062] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0063] Example 1 The preparation process of the self-repairing solid electrolyte membrane of Example 1 is as follows: (1) Dissolve poly (1,4-phenylene sulfide) and LiTFSI in dimethyl sulfoxide to obtain a melt-blown precursor solution, control the screw temperature to 180 °C, and the pulling speed to 50 m / min. -1 , forming a three-dimensional organic skeleton with a porosity of 80%. Based on the total mass of the organic skeleton, the mass of LiTFSI accounts for 20%.

[0064] (2) The compound of formula 1-1, LiTFSI and azobisisobutyronitrile are dissolved in dimethyl sulfoxide to obtain a mixed solution, wherein the mass fraction of dimethyl sulfoxide in the mixed solution is 80%.

[0065] (3) The organic skeleton obtained in step (1) is immersed in the mixed solution obtained in step (2) at a temperature of 25° C. for 5 min. After immersion, the mixture is taken out and vacuum dried at a temperature of 80° C. to obtain a self-healing solid electrolyte membrane. Based on the total mass of the polymer electrolyte (the mass of the self-healing solid electrolyte membrane minus the mass of the organic skeleton), the mass of LiTFSI accounts for 20%, and the thickness of the self-healing solid electrolyte membrane is 60 μm.

[0066] Example 2 The difference between the preparation process of the self-repairing solid electrolyte membrane of Example 2 and the preparation process of the self-repairing solid electrolyte membrane of Example 1 is: In step (2) of Example 2, the polymerizable monomer used is a compound of formula 1-2.

[0067] Example 3 The difference between the preparation process of the self-repairing solid electrolyte membrane of Example 3 and the preparation process of the self-repairing solid electrolyte membrane of Example 1 is: In step (2) of Example 3, the polymerizable monomer used is a compound of formula 1-5.

[0068] Example 4 The difference between the preparation process of the self-repairing solid electrolyte membrane of Example 4 and the preparation process of the self-repairing solid electrolyte membrane of Example 1 is as follows: In step (2) of Example 4, the polymerizable monomer used is a compound of formula 2-1.

[0069] Example 5 The difference between the preparation process of the self-repairing solid electrolyte membrane of Example 5 and the preparation process of the self-repairing solid electrolyte membrane of Example 1 is as follows: In step (2) of Example 5, the polymerizable monomer used is a compound of formula 2-2.

[0070] Example 6 The difference between the preparation process of the self-repairing solid electrolyte membrane of Example 6 and the preparation process of the self-repairing solid electrolyte membrane of Example 1 is: In step (2) of Example 6, the polymerizable monomer used is a compound of formula 2-3.

[0071] Example 7 The difference between the preparation process of the self-repairing solid electrolyte membrane of Example 7 and the preparation process of the self-repairing solid electrolyte membrane of Example 1 is: In step (2) of Example 7, the polymerizable monomer used is a compound of formula 2-4.

[0072] Example 8 The difference between the preparation process of the self-repairing solid electrolyte membrane of Example 8 and the preparation process of the self-repairing solid electrolyte membrane of Example 1 is: The porosity of the organic skeleton obtained in step (1) of Example 8 is 70%.

[0073] Example 9 The difference between the preparation process of the self-repairing solid electrolyte membrane of Example 9 and the preparation process of the self-repairing solid electrolyte membrane of Example 1 is: The porosity of the organic skeleton obtained in step (1) of Example 9 is 60%.

[0074] Example 10 The preparation process of the self-repairing solid electrolyte membrane of Example 10 is as follows: (1) Dissolve poly (1,4-phenylene sulfide) in dimethyl sulfoxide to obtain a melt-blown precursor solution, control the screw temperature to 180 °C, and the pulling speed to 50 m / min. -1 , forming a three-dimensional organic skeleton with a porosity of 80%.

[0075] (2) The compound of formula 1-1, LiTFSI and azobisisobutyronitrile are dissolved in dimethyl sulfoxide to obtain a mixed solution, wherein the mass fraction of dimethyl sulfoxide in the mixed solution is 80%.

[0076] (3) The organic skeleton obtained in step (1) is immersed in the mixed solution obtained in step (2) at a temperature of 25° C. for 5 min. After immersion, the mixture is taken out and vacuum dried at a temperature of 80° C. to obtain a self-healing solid electrolyte membrane. Based on the total mass of the polymer electrolyte (the mass of the self-healing solid electrolyte membrane minus the mass of the organic skeleton), the mass of LiTFSI accounts for 20%, and the thickness of the self-healing solid electrolyte membrane is 55 μm.

[0077] Comparative Example 1 The preparation process of the self-repairing solid electrolyte membrane of Comparative Example 1 is as follows: (1) Dissolve poly (1,4-phenylene sulfide) and LiTFSI in dimethyl sulfoxide to obtain a melt-blown precursor solution, control the screw temperature to 180 °C, and the pulling speed to 50 m / min. -1 , forming a three-dimensional organic skeleton with a porosity of 80%. Based on the total mass of the organic skeleton, the mass of LiTFSI accounts for 20%.

[0078] (2) Dissolving polyvinylidene fluoride and LiTFSI in dimethyl sulfoxide to obtain a mixed solution, wherein the mass fraction of dimethyl sulfoxide in the mixed solution is 80%.

[0079] (3) The organic skeleton obtained in step (1) is immersed in the mixed solution obtained in step (2) at a temperature of 25° C. for 5 min. After immersion, the mixture is taken out and vacuum dried at a temperature of 80° C. to obtain a solid polymer electrolyte membrane. Based on the total mass of the polymer electrolyte (the mass of the solid polymer electrolyte membrane minus the mass of the organic skeleton), the mass of LiTFSI accounts for 20%, and the thickness of the self-healing solid electrolyte membrane is 60 μm.

[0080] Comparative Example 2 The preparation process of the self-repairing solid electrolyte membrane of Comparative Example 1 is as follows: (1) Poly (1,4-phenylene sulfide) and LiTFSI were dissolved in dimethyl sulfoxide to obtain a melt-blown precursor solution. The screw temperature was controlled to be 180°C and the pulling speed was 50 m min-1 to form a three-dimensional organic skeleton. The porosity of the organic skeleton was 80%. Based on the total mass of the organic skeleton, the mass of LiTFSI accounted for 20%.

[0081] (2) Dissolve 2-methyl-3-methylthiofuran, LiTFSI and azobisisobutyronitrile in dimethyl sulfoxide to obtain a mixed solution, wherein the mass fraction of dimethyl sulfoxide in the mixed solution is 80%.

[0082] (3) The organic skeleton obtained in step (1) is immersed in the mixed solution obtained in step (2) at a temperature of 25° C. for 5 min. After immersion, the mixture is taken out and vacuum dried at a temperature of 80° C. to obtain a solid polymer electrolyte membrane. Based on the total mass of the polymer electrolyte (the mass of the solid polymer electrolyte membrane minus the mass of the organic skeleton), the mass of LiTFSI accounts for 20%, and the thickness of the self-healing solid electrolyte membrane is 60 μm.

[0083] Test example In order to verify the performance of the self-repairing solid electrolyte membrane provided by the present invention, the performance of the self-repairing solid electrolyte membrane prepared in each embodiment and comparative example was further tested. The details are as follows: (1) Ionic conductivity test method A stainless steel-self-healing solid electrolyte membrane-stainless steel symmetric battery was assembled and the battery was subjected to electrochemical impedance spectroscopy with a frequency range of 0.1 Hz-1 MHz and a test amplitude of 10 mV.

[0084] (2) Cyclic performance test Assembly of solid-state batteries: 1) Positive electrode: The mass ratio of lithium nickel cobalt manganese oxide, PVDF and conductive carbon black is 8:1:1.

[0085] 2) Use lithium metal negative electrode as the negative electrode.

[0086] 3) Stack the positive electrode sheet, the self-repairing solid electrolyte membrane and the negative electrode sheet in sequence and assemble them into a solid-state battery 4) The battery was tested using the Xinwei battery performance test system with a voltage range of 2.5V-4.2V and a charge and discharge condition of 0.1C cycle at room temperature. The corresponding capacity retention rate was calculated after 100 cycles.

[0087] (3) Tensile strength test method The self-healing solid electrolyte membrane was cut into strips of 8 cm × 2 cm, and the tensile strength was tested using a tensile testing machine at a tensile rate of 20 mm / min.

[0088] The performance test results of the self-repairing solid electrolyte membranes of the embodiments and comparative examples are shown in Table 1.

[0089] Table 1

[0090] As can be seen from Table 1, the batteries of Examples 1-10 all have good tensile strength, high ionic conductivity and excellent cycle performance. Different polymerized monomers are used in Examples 1-7, and the final battery performance will be different. Among them, the battery performance prepared by using the polymerized monomer of Formula 1 is better than that of the battery prepared by using the polymerized monomer of Formula 2. Comparing Example 1 with Comparative Example 1, the battery performance of Comparative Example 1 is significantly worse than that of Example 1, indicating that the polymerized monomer of the present invention can be closely connected and fully fill the pores of the organic skeleton by self-polymerization in the pores of the organic skeleton, which significantly improves the Li + Comparing Example 1 with Comparative Example 2, Comparative Example 2 does not use the polymerized monomer of the present application, and the battery performance of Comparative Example 2 is poor in all aspects, indicating that the presence of -SS- in the polymerized monomer of the present invention gives the electrolyte membrane self-repairing ability, greatly improving the tensile strength of the self-repairing solid electrolyte membrane.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A self-repairing solid electrolyte membrane, characterized in that: include: Organic framework; A polymer electrolyte is filled in the pores of the organic skeleton. The polymer electrolyte is formed by polymerizing a polymer monomer and a first lithium salt in the pores of the organic skeleton. The polymer monomer contains a self-repairing SS bond, and the polymer monomer also contains a CO bond and a C=C bond.

2. The self-repairing solid electrolyte membrane according to claim 1, characterized in that: The polymerizable monomer is selected from at least one of the compounds represented by Formula 1 and the compounds represented by Formula 2; , wherein -R1, -CH3, -SS-R2 groups are substituted at any position above, R1 is selected from hydrogen or methyl, and R2 is selected from C1-C5 alkyl or epoxy; , wherein -R3, -CH3-SS-R4 groups are The above substituted at any position, R3 is selected from hydrogen or methyl, R4 is selected from C1-C5 alkyl or epoxy.

3. The self-repairing solid electrolyte membrane according to claim 2, characterized in that: R2 is selected from methyl, ethyl, propyl, butyl, , or ; and / or, R4 is selected from methyl, ethyl, propyl, butyl, or .

4. The self-repairing solid electrolyte membrane according to claim 3, characterized in that: The compound represented by the general formula 1 includes at least one of the following structures: 、 、 、 、 、 ; And / or, the compound represented by the general formula 2 comprises at least one of the following structures: 、 、 、 。 5. The self-repairing solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The organic framework includes a polymer and a second lithium salt; and / or, the organic framework is a fibrous structure; and / or, the porosity of the organic framework is 60% to 80%; And / or, the polymer includes at least one of polystyrene, poly-2,6-dimethyl-1,4-phenylene oxide, polyimide, poly-1,4-phenylene sulfide, polyphthalaldehyde, polystyrene-acrylonitrile, polystyrene-butadiene, polyphenylmethylsiloxane, polystyrene-allyl alcohol, polyvinyl benzene sulfide, poly-4-butyltriphenylamine, polystyrene-divinylbenzene, poly-4-vinylpyridine-styrene, polybis(4-phenyl)(4-butylphenyl)amine and polysulfone, preferably poly-1,4-phenylene sulfide and polyvinyl benzene sulfide; And / or, based on the total mass of the organic skeleton, the mass proportion of the second lithium salt is 5-50%, preferably 20-50%.

6. The self-repairing solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: Based on the total mass of the polymer electrolyte, the mass proportion of the first lithium salt is 5-50%, preferably 20-50%; And / or, the polymer electrolyte further comprises an inorganic filler, and the mass proportion of the inorganic filler is 5-30%, preferably 20-30%, based on the total mass of the polymer electrolyte; And / or, the thickness of the self-repairing solid electrolyte membrane is 50 μm to 80 μm.

7. A method for preparing the self-repairing solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: include: The organic skeleton is immersed in a mixed solution containing a polymerized monomer, a first lithium salt, an initiator and a first solvent, and then dried to obtain a self-repairing solid electrolyte membrane.

8. The method according to claim 7, characterized in that: The mass proportion of the first solvent of the mixed solution is 70% to 90%, preferably 70% to 80%; And / or, the drying temperature is 60°C to 100°C, preferably 60°C to 80°C; And / or, the soaking time is 5 min to 10 min, and the temperature is 25° C. to 30° C.; And / or, the method for preparing the organic skeleton comprises: dissolving a polymer and a second lithium salt in a second solvent and then performing melt-blowing to obtain the organic skeleton.

9. A solid-state battery, characterized in that: It comprises the self-repairing solid electrolyte membrane described in any one of claims 1 to 6 or a self-repairing solid electrolyte membrane prepared by the method described in claim 7 or 8.

10. A mechanical device, characterized in that: Comprising the solid-state battery as described in claim 9.

Citation Information

Patent Citations

  • All-solid-state composite electrolyte as well as preparation method and application thereof

    CN113381060A

  • Battery preparation method using in-situ polymerization interface self-repairing polymer electrolyte

    CN118367224A

  • Conductive polymer, solid electrolytic capacitor and production thereof

    JP2000239361A

  • Electrolyte membrane for all-solid state battery and all-solid state battery including the same

    US20220294001A1

  • Electrolyte system

    WO2024201348A1

Cited By

  • All-solid-state polymer electrolyte membrane for lithium battery as well as preparation method and application of all-solid-state polymer electrolyte membrane

    CN120690913A

  • A full-solid-state polymer electrolyte membrane for lithium batteries and a preparation method and applications thereof

    CN120690913B

  • Gel polymer electrolyte membrane for lithium battery as well as preparation method and application of gel polymer electrolyte membrane

    CN120978186A

  • Self-repairing sulfur-containing polymer electrolyte membrane for lithium battery as well as preparation method and application of self-repairing sulfur-containing polymer electrolyte membrane

    CN121035329A

  • Self-repairing sulfur-containing polymer electrolyte membrane for lithium battery and preparation method and application thereof

    CN121035329B